2006
DOI: 10.1097/00000542-200610000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Severe Toxic Damage to the Rabbit Spinal Cord after Intrathecal Administration of Preservative-free S  (+)-Ketamine

Abstract: The authors conclude that repeated intrathecal administration of preservative-free S(+)-ketamine in a clinically relevant concentration and dosage has, considering the extent and severity of the lesions, a toxic effect on the central nervous system of rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 0 publications
4
55
0
2
Order By: Relevance
“…It has been reported that ketamine HCl administered via IT provides sensory and motor blockage both by its antagonist effect on NMDA receptors and by blocking calcium channels (7,12,13,(15)(16)(17)19). The purpose of this study was to use these characteristics of IT administration of ketamine and evaluate its efficacy on calves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that ketamine HCl administered via IT provides sensory and motor blockage both by its antagonist effect on NMDA receptors and by blocking calcium channels (7,12,13,(15)(16)(17)19). The purpose of this study was to use these characteristics of IT administration of ketamine and evaluate its efficacy on calves.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that it provides sensory and motor blockage when administered via IT (7,17). Its action is based on two mechanisms: ketamine is an antagonist of the N methyl-D aspartate (NMDA) receptors located in the dorsal root of the spinal cord (15,16,17,19), and it reduces depolarisation by blocking the sodium channels similarly to local anaesthetics (7,12,13,15,17,18). In addition, it is claimed that ketamine is beneficial for the respiratory system due to its bronchodilator effect (10,12,16).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Vranken et al, preservative-free ketamine applied intrathecally in rabbits for 7 days resulted in no significant changes among motor functions, although axonal swelling and chromatolysis were high, suggesting a toxic damage. 21 When Gomes et al applied preser-…”
Section: Discussionmentioning
confidence: 99%
“…After repeated intrathecal delivery in rabbits [197] or continuous infusion in dogs [198], Ketamine and a number of other NMDA channelblocking antagonists including MK-801, dextrorphan, dextromethorphan and memantine and the nonopiate agent D-methadone, and to a lesser degree the glutamate antagonist 2AP5,resulted in prominent spinal pathology reflecting parenchymal necrosis in dogs and/or sheep [198,199]. These spinal effects, where examined, appear to be concentrationdependent and, with the exception of the neonatal model, the therapeutic ratio (e.g., therapeutic dose/minimum toxicity dose-concentration) has not been defined.…”
Section: Adverse Eventsmentioning
confidence: 99%